AKTIVITAS DAN RESPON SISWA MELALUI MODEL PEMBELAJARAN WITHIN-SOLUTION POSING - Susiaty, Utin Desy (Universitas PGRI Adi Buana Surabaya, 2018)
The purpose of this study was to describe the activities and responses of students through the in-solution posing learning model. This research uses quantitative approach with descriptive method. The population in this study is the students of class VII MTs Negeri 2 Pontianak academic year 2007/2008 who studied the material of comparative value and turned the value. The result of the research shows that students of Grade VII MTs Negeri 2 Pontianak are active in learning with within-solution posing and VII students of MTs Negeri 2 Pontianak give positive response to learning with within-solution posing. Keywords: activities, response, within -solution posing